ELECTRONIC DIGITAL SIGNATURE PROTOCOL ON THE BASIS OF ASYMMETRIC ENCRYPTION ALGORITHM BASED ON THE DIFFICULTY OF DISCRETE LOGARIFICATION AND MULTIPLICATION OF MATRIXES WITH A PARAMETER ON A FINAL FIELD - Sh. Sh. Akhmadaliev (Galaxy International Interdisciplinary Research Journal, 2022)
In article the report of the electronic digital signature on the basis of asymmetric algorithm of the enciphering based on complexity discrete taking the logarithm and multiplication of matrixes with parameter on a final field at which, in formation of the digital signature there is a possibility of a choice of any number from the signed is developed.